Anti-leishmanial activity of Brevinin 2R and its Lauric acid conjugate type against L. major: In vitro mechanism of actions and in vivo treatment potentials - Zahedifard, Farnaz; Lee, Hyeryon; No, Joo Hwan; Salimi, Mona; Seyed, Negar; Asoodeh, Ahmad; Rafati, Sima (PLOS Neglected Tropical Diseases, 2019)
Leishmaniasis, as a major health problem in tropical and sub-tropical areas in the world, needs novel, safe, nontoxic and plausible therapeutic solutions for its control. As a part of innate immune system, natural antimicrobial peptides have a potential to be used as new generation of antibiotics especially after persistent resistance of conventional antimicrobial agents. Brevinin 2R, a member of Defensin families of host defense peptides, showed promising effects against bacterial and fungal infections as well as cancerous cell lines. In the current research, the anti-leishmanial effect of Brevinin 2R and its lauric acid conjugate was investigated against Leishmania major (L. major) parasite. The data revealed that, conjugation of fatty acid to Brevinin 2R, strengthen its effect on L. major promastigotes as well as toxicity and hemolytic effect. These peptides showed anitleishmanial activity through cell membrane disruption and changes in the electrical and mitochondrial membrane potential. No signs of apoptosis induction or caspase activation were detected. Despite its hemolytic and cytotoxic effect in in vitro conditions, lauric acid- Brevinin 2R (L- Brevinin 2R) did not show site specific adverse reactions in animal model. Treatment course with L- Brevinin 2R in the L. major infected mice exhibited decreased parasite load in the lymph nodes adjacent to the infected site despite cytokine production profile and footpad swelling data.